2020
DOI: 10.1108/jitlp-08-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

China’s blocking mechanism: the unreliable entity list

Abstract: Purpose The purpose of this paper is to seek to break the deadlock of the current confrontations between the two powers. Design/methodology/approach The paper is comparative and theoretical. Findings The findings suggest that multinational corporations would be put between a rock and a hard place. Originality/value Only multi-pronged approaches could be viable to address the issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…This broadens the scope of the Provisions beyond the prohibition of complying with foreign sanctions. It was suggested that determination of “normal market transaction principles” could follow the standards applied by China’s competition authorities when enforcing prohibition of abuse of dominance in the form of refusal to deal under China’s Anti-Monopoly Law (Bu, 2020). It would require the authorities to ascertain whether termination of business relationship was commercially unreasonable and thus not motivated by “normal market transaction principles”.…”
Section: Confronting Extraterritoriality: China’s Legal Framework Aga...mentioning
confidence: 99%
“…This broadens the scope of the Provisions beyond the prohibition of complying with foreign sanctions. It was suggested that determination of “normal market transaction principles” could follow the standards applied by China’s competition authorities when enforcing prohibition of abuse of dominance in the form of refusal to deal under China’s Anti-Monopoly Law (Bu, 2020). It would require the authorities to ascertain whether termination of business relationship was commercially unreasonable and thus not motivated by “normal market transaction principles”.…”
Section: Confronting Extraterritoriality: China’s Legal Framework Aga...mentioning
confidence: 99%
“…The entity list system is an important part of the U.S. export administration's regulations and serves the country's strategic interests and foreign policy. It is controlled by the Bureau of Industry and Security in the U.S. Department of Commerce and used to list entities that the U.S. government believes to be involved in or have a significant risk of participating in activities that harm U.S. national security or economic interests (Bu, 2020). This means that blacklisted firms need to apply for special permission to import goods or technologies from the United States.…”
Section: Introductionmentioning
confidence: 99%